2004
DOI: 10.1101/gad.1238604
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of the Escherichia coli σE envelope stress response relies on multiple mechanisms to inhibit signal-independent proteolysis of the transmembrane anti-sigma factor, RseA

Abstract: Proteolytic cascades are widely implicated in signaling between cellular compartments. In Escherichia coli, accumulation of unassembled outer membrane porins (OMPs) in the envelope leads to expression of E -dependent genes in the cytoplasmic cellular compartment. A proteolytic cascade conveys the OMP signal by regulated proteolysis of RseA, a membrane-spanning anti-sigma factor whose cytoplasmic domain inhibits E -dependent transcription. Upon activation by OMP C termini, the membrane localized DegS protease c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 36 publications
3
127
0
Order By: Relevance
“…The mechanistic details underlying this are unknown; however DegS, RseB, the periplasmic domain of RseA, and the PDZ domain of RseP participate in at least two independent mechanisms to repress activity of this protease toward full-length RseA (Kanehara et al 2003;Bohn et al 2004;Grigorova et al 2004). We have suggested that RseP cleavage of full-length RseA is blocked so that DegS cleavage of RseA will be rate-limiting over a wide range of OMP signal.…”
Section: Organization Of the Proteolytic Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic details underlying this are unknown; however DegS, RseB, the periplasmic domain of RseA, and the PDZ domain of RseP participate in at least two independent mechanisms to repress activity of this protease toward full-length RseA (Kanehara et al 2003;Bohn et al 2004;Grigorova et al 2004). We have suggested that RseP cleavage of full-length RseA is blocked so that DegS cleavage of RseA will be rate-limiting over a wide range of OMP signal.…”
Section: Organization Of the Proteolytic Cascadementioning
confidence: 99%
“…However, when porin C termini bind to the DegS PDZ domain, the catalytic triad is repositioned and cleavage of RseA ensues (Walsh et al 2003;Wilken et al 2004). DegS, RseB, RseA, and the PDZ domain of RseP itself all inhibit RseP cleavage of intact RseA, thereby ensuring that DegS always acts before RseP in the RseAprocessing pathway (Kanehara et al 2003;Bohn et al 2004;Grigorova et al 2004). Since DegS is the only protease that senses the porin signal, obligate sequential cleavage of RseA ensures that the initiation of the proteolytic cascade reflects the status of this inducing signal.…”
mentioning
confidence: 99%
“…Under environmental conditions that elevate ECF s factor activity, many integral membrane anti-s factors undergo RIP, as is the case for anti-s factors regulating s E from E. coli and s W and s V from B. subtilis (Chaba et al, 2007;Grigorova et al, 2004;Hastie et al, 2014;Ho & Ellermeier, 2012). RIP is initiated by a highly specific site-1-protease (S1P).…”
Section: Discussionmentioning
confidence: 99%
“…This sequential digestion of RseA results in the release of E , which ultimately enhances the transcription of the gene involved in stress response (Alba et al, 2002;Kanehara et al, 2002). RseB prevents the proteolytic cleavage of RseA by binding to the periplasmic region of RseA (Missiakas et al, 1997;Grigorova et al, 2004). It is thought that the role of RseB is essential for the negative regulation of E signalling, since RseP alone can cleave RseA in a cell in which RseB and DegS are null-mutated (Grigorova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…RseB prevents the proteolytic cleavage of RseA by binding to the periplasmic region of RseA (Missiakas et al, 1997;Grigorova et al, 2004). It is thought that the role of RseB is essential for the negative regulation of E signalling, since RseP alone can cleave RseA in a cell in which RseB and DegS are null-mutated (Grigorova et al, 2004). RseB has also been proposed to activate the function of E by sensing other stress signals, including damaged proteins in periplasmic space.…”
Section: Introductionmentioning
confidence: 99%